Assessing minimum standard requirements and Sharia compliance for Muslim’s cemetery at urban setting - Othman, Jamilah; Albakeri, Norsyaza Husna (Science Publishing Group, 2019)
The paper documents a study on the Minimum Standard Requirements (MSRs) and Sharia compliance of a Muslim’s cemetery on Jalan Ampang, Kuala Lumpur, Malaysia. The site was selected, due to the historical and socio-cultural values that it holds amongst the urban community. The paper aimed to assess the existing infra development and planning layout of the landscape based on multiple methods of data collections (e.g., review of literature, site observation, and questionnaire survey). A finding shows that the crowded cemetery implicates a grave-finding location and pedestrian circulation within the sacred landscape. The result also suggests that lack of good landscape maintenance and management practices influence the visual quality of the landscape, which indirectly influences the image of the capital city of Kuala Lumpur. Hence, this study has merits because it provides objective solution to assist stakeholders to consider establishing a Muslim’s cemetery at an urban setting using MSRs of infra that comply with the Sharia.